1991
DOI: 10.1007/bf01627759
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy and histology of the radial artery and the internal thoracic artery

Abstract: Anatomical characteristics of the radial a. were compared to those of the internal thoracic a., considered as a gold standard in coronary surgery. The length, the diameter, the collateral distribution and the wall thickness of these two arteries were studied comparatively. In addition, a comparative histological analysis was carried out. Anatomical and histological characteristics of these two arteries have important implications for coronary artery bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
7

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 6 publications
1
30
0
7
Order By: Relevance
“…46 Although patients with ESRD have increased risk of accelerated atherosclerosis, 47,48 the described changes of the arterial wall are independent of this parameter since they have been shown to be present at the level of the radial artery, where atherosclerosis is practically absent. 44,49 Recently, Blacher et al 26 have demonstrated that increased aortic PWV is an independent risk factor of all-cause and CV mortality in haemodialysed patients, a finding recently confirmed by therapeutic trial. 50 All these previous studies have been conducted in patients with advanced uraemia.…”
Section: Pulse Wave Velocity Pulse Pressure and Renal Failurementioning
confidence: 94%
“…46 Although patients with ESRD have increased risk of accelerated atherosclerosis, 47,48 the described changes of the arterial wall are independent of this parameter since they have been shown to be present at the level of the radial artery, where atherosclerosis is practically absent. 44,49 Recently, Blacher et al 26 have demonstrated that increased aortic PWV is an independent risk factor of all-cause and CV mortality in haemodialysed patients, a finding recently confirmed by therapeutic trial. 50 All these previous studies have been conducted in patients with advanced uraemia.…”
Section: Pulse Wave Velocity Pulse Pressure and Renal Failurementioning
confidence: 94%
“…16 Such findings are observed on central elastic and peripheral muscular arteries. 10,11,16 In particular, in vivo studies performed on the radial artery, a blood vessel poorly altered by aging and unmodified by atherosclerosis, 17 have shown that the major mechanism of vascular alterations was characterized by an increased stiffness of the vascular wall matrix, 18,19 a parameter consistently associated to "uremia" and not to high blood pressure. Studies in experimental uremia and in vitro in arteries of uremic patients have shown striking structural alterations involving an increase in wall thickness, cross-sectional media, and total extracellular matrix including collagen but no elastin.…”
Section: Large Artery Damage In End-stage Renal Diseasementioning
confidence: 99%
“…2,3 Because the Einc of the CCA is increased independently of BP and wall stress, the role of mechanical factors in the mechanism of elevated Einc does not seem dominantly involved. 2 Because higher values for Einc have been observed at the site of the radial artery, which is consistently devoid of atherosclerosis, 4 the "accelerated atherosclerosis" described in ESRD patients 5,6 does not seem responsible for this increase in Einc. Thus, it is relevant to determine in patients with ESRD whether biochemical and/or structural factors related to kidney alterations might influence the changes in Einc.…”
mentioning
confidence: 99%